Seismic analysis of building frame by using Visco-elastic damper - Ghodake, K.G.; Suryawanshi, N.T. (Journal of Structural Engineering, 2025)
During the earthquakes of Bhuj and Ahmdabad many multistoried building have suffered wide spread damage. Post earthquake observations have sighted various reasons for such large scale damages such as poor quality of constructions, lack of seismic resistant features etc. The deficient features can be eliminated through strict enforcement of guide lines and regulations. Seismic performance of buildings can also be improved with the help of energy absorbing devices. Active and passive devices have been proposed. Active control techniques have not found much appreciations due to its high cost and large instrumentation set up. Passive devices include viscous dampers, visco-elastic dampers, friction dampers and tuned mass damper. This paper deals with the use of visco-elastic damper. It also includes the effect of visco-elastic dampers on structural response of plane frames. Comparative study between plane frame with and without visco-elastic dampers were carried out and from the study it is found that visco-elastic dampers minimizes displacement as well as drift.